Potential of Anti Breast Cancer Black Ethanol Rice Extract (Oryza sativa L). indica) In Decreasing Levels of CA 15-3 Serum in the White Mice Sprague dawley in Induction 7.12-Dimethylbenz (α) Antracene (DMBA) and Estrogen - Zanuar Abidin (Universitas Muhammadiyah Surabaya, 2017)
Breast cancer is cancer that has the high incidence in Indonesia. Black rice (Oryza sativa L. indica) is a plant that has an anticancer potency. This research aim is to prove black rice as a potential anticancer by using experimental animals, 20 Sprague Dawley female rats aged 7-8 weeks induced breast cancer by using the combination of 7,12-dimethylbenz (α) anthracene (DMBA) and estrogen. Rats were divided into two groups, namely the K-induced breast cancer and a group of P-induced cancer and treated with black rice. Black rice is given in the form of ethanol extract at a dose of 75 mg / kg / day for six weeks. Levels of CA 15-3 serum are used as a parameter. The result showed that the differences in levels of serum CA 15-3 are significant (p <0.05). Serum CA 15-3 level in P group is lower than in K group. This study proved that the ethanol extract of black rice (Oryza sativa L. indica) has potential as an anticancer breast as indicated by decreased level of serum CA 15-3